Celowość i warunki skuteczności wdrożenia strategii ekologicznej w przedsiębiorstwie - Połomska-Jasienowska, Agnieszka (Suitableness and Conditions of Efficacy of Implementation of Ecological Strategics, 2006)
"This article describes suitableness and conditions of efficacy of implementing ecological strategics. The main reason is increasing norms of law and increase in ecological costs and ecological duties. Another cause is rising ecological consciousness. The firms which want to change their effigy have to settle goals which help them change the process of production."
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 449-456